Literature Review: The Use of Tetrahedral Chemistry Representation in Chemistry Learning - Rosy Novita; Faizah Qurrata Aini (Entalpi Pendidikan Kimia, 2022)
Chemistry is a science that studies phenomenology and abstraction. Then chemistry is related to all things that exist in nature. Therefore, this study aims to discuss the use of tetrahedral chemistry representation in chemistry learning. The research method used is literature study or library research. Meanwhile, the data sources used are secondary data obtained from various sources such as journals, books, and other sources relevant to the research. The results showed that learning with tetrahedral chemistry representation is very suitable for 21st century learning and the 2013 curriculum. The use of tetrahedral chemistry representation can help in understanding abstract concepts. Then students can use chemistry appropriately to solve complex problems in real life. The tetrahedral chemistry representation can also define and design the future of chemistry and chemistry education